THE DEVELOPMENT OF A TRAINING CURRICULUM FOR ENHANCING SPEECH LANGUAGE AND COMMUNICATION SKILLS FOR PARENTS OF CHILDREN WITH SPECIAL NEEDS BASED ON PROBLEM-BASED LEARNING AND COACHING AND MENTORING - Phoommisittiporn, Anucha (Journal of Education and Innovation, 2026)
The purposes of this study are to: 1) investigate the fundamental information necessary for development of a training curriculum, 2) develop the training curriculum, 3) implement the training curriculum, and 4) evaluate the training curriculum. The participants were 30 Parents of Children with Special Needs in Phitsanulok Province, who were selected using purposive sampling. The instrument used in this study included the Training Curriculum. Data were analyzed using mean, standard deviation, and t-test. The findings can be summarized as follows: 1) The study of foundational information indicated that the problems and needs related to the enhancement of Speech Language and Communication Skills among Parents of Children with Special Needs were, overall, at the highest level. And the content of the training curriculum should comprehensively cover both theoretical knowledge and practical skills, and the development of the training curriculum should focus on promoting Problem-based Learning and Coaching and Mentoring. 2) The training curriculum comprises five components: principles, objectives, content, training activities, and assessment and evaluation. It was developed based on promoting Problem-based Learning and Coaching and Mentoring. The results of the quality evaluation showed that the training curriculum was rated at the highest level of appropriateness. 3) The experimental results indicated that, after the implementation of the training curriculum, parents of children with special needs demonstrated competencies and assessment results in promoting speech, language, and communication skills that were significantly higher than the pre-test scores, with statistical significance at the .05 level, and 4) the results of the training curriculum evaluation indicated that, overall, the quality of the training curriculum in terms of context, input, process, and product was at the highest level.